2019
DOI: 10.1016/j.bbmt.2018.12.254
|View full text |Cite
|
Sign up to set email alerts
|

Phase I, Dose Escalation Study of Naïve T-Cell Depleted Donor Lymphocyte Infusion Following Allogeneic Stem Cell Transplantation

Abstract: GVHD (Figure 3B). We observed no difference in IL-15, CXCL10 and CXCL9 levels in patients with and without GVHD. Conclusion: Maraviroc administration was feasible in children but was limited by elevated bilirubin levels and transaminases, unrelated to maraviroc. We achieved successful CCR5 blockade but also observed breakthrough of GVHD due to failure to administer maraviroc consistently. Peripheral blood activation of T-cell lymphocytes occurs in patients with imminent acute GVHD despite maraviroc prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A single‐arm experience with a limited number of patients (n = 35) showed that the incidence of grade II‐IV aGvHD was up to 66% in a MRD cohort, which was not reduced as expected, but the incidence of chronic GvHD was only 9% 27 . However, another phase I dose escalation study found that the maximum administered cell dose of 1 × 10 7 CD3+ cells/kg DLI depleted of CD45RA+ Tn cells did not result in clinically significant acute GvHD in patients following HLA‐identical HSCT 28 . More recently, selective CD45RA T‐cell depletion has been proven to reduce viremia and enhance early T‐cell recovery compared to CD3‐depleted T cells in haploidentical cohorts.…”
Section: To Optimize Graft Composition By Graft Engineeringmentioning
confidence: 84%
“…A single‐arm experience with a limited number of patients (n = 35) showed that the incidence of grade II‐IV aGvHD was up to 66% in a MRD cohort, which was not reduced as expected, but the incidence of chronic GvHD was only 9% 27 . However, another phase I dose escalation study found that the maximum administered cell dose of 1 × 10 7 CD3+ cells/kg DLI depleted of CD45RA+ Tn cells did not result in clinically significant acute GvHD in patients following HLA‐identical HSCT 28 . More recently, selective CD45RA T‐cell depletion has been proven to reduce viremia and enhance early T‐cell recovery compared to CD3‐depleted T cells in haploidentical cohorts.…”
Section: To Optimize Graft Composition By Graft Engineeringmentioning
confidence: 84%
“…In our case, the depletion was very efficient and CD45RA was undetectable. Recently, there had been published phase 1 dose escalation study result on CD45RA depleted DLI, with maximum cell dose set at 1 × 10 7 /kg, 27 which was the cell dose administered to our patient in the 2 DLIs.…”
Section: Controversy On Cell Dose and Dosing Interval Of Cd45ra-depleted DLI And Use Of Atg Prior To Dlimentioning
confidence: 99%
“…Furthermore, low immunogenicity of some T-cell epitopes (e.g., Epstein-Barr nuclear antigen 1, EBNA1) also causes problems [19]. Consequently, strategies to refine DLIs through selective T N depletion were developed to obtain antiviral memory T-cell products with the potential to protect patients from viral infection/reactivation while reducing the risk of GvHD occurrence [20-22].…”
Section: Introductionmentioning
confidence: 99%